Exile and homesickness in the poetry of Ahmad Shawqi - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2021)
Ahmad Shawqi was raised in the royal palace, where his maternal grandmother – who sponsored him after the death of his mother – was a favoured maid at Khedive Ismail. Shawqi studied law in Egypt and Paris, and when he returned to Egypt, he became poet Laurette for Khedive Abbas Helmy II. Although Shawqi was brought up in the royal palace, as a poet, he felt the pulse of the Egyptian people and felt their pain and dreams. After the First World War broke out, in 1915, Shawqi was exiled to Spain where he was swept away by longing for his homeland. During his exile, the 1919 revolution erupted in Egypt, and his longing for his homeland intensified, and obsessed his heart and soul. Exile was the greatest ordeal that Shawqi went through in his life. In exile, he did not find relief except when resorting to his poetry, to which he revealed the pains of his heart. He also visited the memorials of the Muslims and their reign and civilization in Seville, Cordoba, and Granada. This resulted in Shawqi composing his lengthy poem “Arab countries and the greats of Islam”. Shawqi’s poems are considered masterpieces for their sincerity of emotion and beauty of description. Perhaps the most famous of these is The Seeniya; rhyming with the letter S, entitled “The Journey to Andalusia”, and his other longing poem, “The Nouniya; rhyming with the letter N”, in which he opposed the famous medieval Arab Andalusian poet, Ibn Zaidoun.